Genummerd + Gesigneerd 1. (Venlo : Museum Van Bommel Van Dam, 1995)
Veneman, Peer ; Klashorst, Peter ; Heikens, Harma ; Schuil, Han ; Bolink, Merijn ; Schabracq, Alexander ; Blanca, Paul ; Neary, Scott ; Polhuis, Gerard ; Uglow, Alan ; Leyenaar, Jorgen ; Lucassen ; etc.
Genummerd + Gesigneerd 1, Museum Van Bommel Van Dam, Venlo, 17 september tot en met 5 november 1995
Nederlands
kunstcatalogus